KOMUNITAS FACEBOOK PERWIRA GRABMERCHANT JAWA TIMUR SEBAGAI MEDIA PEMBERDAYAAN UMKM DI MASA PANDEMI COVID-19 (The Commercium, 2023)
The extraordinary economic shock during the COVID-19 pandemi caused many MSMEs to experience a significant decrease in turnover. So that there is a need for provision and direction for MSMEs in running their business through empowering MSMEs digitally where they can still run their business through an online system (e-marketing), one of which is through the PERWIRA GrabMerchant East Java Facebook Community. This research aims to increase knowledge regarding the role of virtual communities, especially the role of the East Java PERWIRA GrabMerchant Facebook Community as a medium for empowering MSMEs that can help their partners during the COVID-19 pandemi, and can find out about how group communication occurs in the community. This research is a qualitative descriptive research with a case study method. Data collection was obtained through observation and interviews. The results of this research show that the East Java PERWIRA GrabMerchant Facebook Community plays an important role as a medium for empowering MSMEs through various programs implemented exclusively for community members / MSMEs who are members of Grabfood partners / merchants.